Connectors with assessed quality, for use in d.c., low-frequency analogue and in digital high speed data applications. Printed board connectors. Detail specification for two-part connector modules having a basic grid of 2, 0 mm for printed boards and backplanes in accordance with IEC 60917 Part 4-101, (15th October 1998) - British Standards Institution,
No abstract available